Clinical, Dermoscopic and Microscopic Features of a “Collision Tumour” Ultimately Confirmed as a Regressing Melanoma – Lessons Learnt from a Chance Diagnosis - Nwabudike LC; Oproiu AM; Dogaru IM; Costache M; Tatu AL (Dove Medical Press, 2022)
Lawrence Chukwudi Nwabudike,1 Ana Maria Oproiu,2,3 Ioana Mihaela Dogaru,2,3,* Mariana Costache,3,4,* Alin Laurentiu Tatu5- 7 1Outpatient Dermatology, N. Paulescu National Institute of Bucharest, Bucharest, Romania; 2Department of Plastic Surgery, Emergency University Hospital, Bucharest, Romania; 3Carol Davila University of Medicine and Pharmacy, Bucharest, Romania; 4Department of Pathology, Emergency University Hospital, Bucharest, Romania; 5Clinical Medicine Department, Faculty of Medicine and Pharmacy, Dunarea de Jos University of Galati, Galati, Romania; 6Dermatology Department, St Parascheva Clinical Hospital of Infectious Diseases, Galati, Romania; 7Multidisciplinary Integrated Center for Dermatologic Interface Research (MIC-DIR), Galati, Romania*These authors contributed equally to this workCorrespondence: Lawrence Chukwudi Nwabudike, N. Paulescu Institute of Bucharest, 5-7 Ion Movila Street, Sector 2, Bucharest, Romania, Email Chukwudi.nwabudike@live.com Ana Maria Oproiu, Carol Davila University of Medicine and Pharmacy, Bucharest, Romania, Email anamariaoproiu@gmail.comAbstract: Spontaneous regression of malignant melanoma was first reported over a century ago. Clinically, areas of blue or grey colouration in lesions may be indicative of regression. Dermoscopy is a very useful tool for diagnosing regression. An important criterion is the blue-white scar. About 10- 35% of excised melanomas show features of regression histopathologically. We present a case of regressing melanoma, with clinical and dermoscopic features suggesting a collision tumour, diagnosed histopathologically. This case might improve our knowledge of the potential clinical manifestations, and the biology, of regressing melanoma.Keywords: regressing melanoma, collision lesion, blue-white scar, pepper-like granules, milia-like cysts, pseudofollicular openings